Autonomous horticulture irrigation system - Sabri, Mohd Tahir (2016)
Plant need enough water to grow green and healthy. Sometime people cannot maintain their watering activities. Autonomous Horticulture Irrigation System is develop to manage horticulture irrigation activity. It will be based on Internet on Things (IoT) project which user can receive a notification and remotely control the irrigation process. In this system, the sensor will be the input device to read the moisture condition of soil. The system will receive the data and decide if the soil is wet, or dry and need for watering. The system will send notification to remind user for irrigation process. Autonomous Horticulture Irrigation System will handle systematic watering activity, hence keep the soil on good moisture and update data condition to the user. Rapid Application Development methodology is applied as a guideline development of the project. RAD methodology it is an ideal methodology for this project as it is very flexible and adjustable to redesign. As results, the system will produce systematic management to horticulture activity. In conclusion, the proposed system aims to improve the way people managing plants and maintain the moisture of soil needed by a plant.